A Rare Case of Checkerboard-Like Becker Nevi with a Unique Distribution of Abnormalities. (14th May 2019) - Wongtada, Chanidapa; Asawanonda, Pravit; Pongprutthipan, Marisa
Abstract : Becker nevus syndrome refers to a rare disorder comprising the typical pigmented lesion and its associated developmental abnormalities. Becker nevus itself is typically localized on the upper trunk, scapular or upper arm unilaterally; however, it can occasionally occur as multiple or bilateral lesions on any parts of the body. In this report, a rare case of multiple Becker nevi arranged in a unique checkerboard-like pattern is presented. More uniquely, the associated abnormalities found in this patient, breast hypoplasia and leg lipodystrophy, seem to be regionally correlated with the nevi. In closing, we would like to raise an easy-to-remember 6B's mnemonic, which stands for Becker, Breast, Bone, Bowen's disease, Basal cell carcinoma, and Beta-actin, for the cases of Becker nevus syndrome.